The history and transformation of Perak Malay traditional house / Sabrizaa Rashid, Nurfaisal Baharuddin and Kartina Alauddin - Rashid, Sabrizaa; Baharuddin, Nurfaisal; Alauddin, Kartina (Universiti Teknologi MARA, Perak, 2021)
Apart from shelter, traditional houses were built to accommodate the spiritual factors such as religious, cultural values and way of life. Thus, it tends to evolve over time to reflect the environmental, cultural, technological and historical context in which it exists. This paper discusses the development of architectural style on the Malay traditional houses in Perak. It is based on data collectively gathered from KUTAI researchers conducted since 1997. More than 400 houses were observed. Architectural transformation found in the roof design, spatial organization, architectural elements and decorative elements within the period of 150 years. Findings of this study strengthening and establish the Perak Malay architectural style.